Sex-specific prevalence and risk factors of metabolic-associated fatty liver disease among 75,570 individuals in eastern China - Chang, Mingxing; Shao, Zhihao; Wei, Wei; Shen, Peipu; Shen, Guifang (Frontiers in Endocrinology, 2023)
Background Metabolic-associated fatty liver disease (MAFLD) is a newly proposed definition and there is limited data on MAFLD prevalence. We aimed to investigate the prevalence of MAFLD in an eastern Chinese population.This cross-sectional study included participants from an eastern Chinese population who underwent regular health checkups. Based on current diagnostic criteria, MAFLD was diagnosed in individuals with both hepatic steatosis and metabolic disorders. The overall and stratified prevalence derived based on sex, age, body mass index (BMI), and various metabolic disorders were estimated.Multivariate logistic regression analysis was used to determine the risk factors for MAFLD.Among the 75,570 participants, the overall prevalence of MAFLD was 37.32%, with higher rates in men (45.66%) than in women (23.91%). MAFLD prevalence was highest in men aged 40-49 years (52.21%) and women aged 70-79 years (44.77%). In all the BMI subgroups, the prevalence was higher in men than in women. In both sexes, the prevalence of MAFLD increased as BMI levels increased. Furthermore, MAFLD was associated with metabolic disorders, especially in the female participants with severe obesity (odds ratio 58.318; 95% confidence interval: 46.978-72.397).Conclusions MAFLD is prevalent in the general adult population in eastern China. Sex-specific differences in MAFLD prevalence were identified based on age, BMI, and metabolic disorders.MAFLD is associated with metabolic disorders, particularly obesity.